BUSINESS LEVEL STRATEGY & DIVERSIFICATION ANALYSIS at MCDONALD'S - Fikra Terisha Azzikra; Jessica; Putri Sahara; Senly (Asosiasi Dosen Muda Indonesia, 2023)
In the business world, there is a hierarchy of strategies that empower organizations to achieve organizational goals more effectively and efficiently, namely Business Level Strategy and Corporate Level Strategy. The purpose of this study is to discuss how McDonalds implements these two strategies to achieve organizational goals and gain competitive advantage. In this study, a qualitative approach was used. By implementing a Business Level Strategy by choosing the Integrated Cost Leadership Differentiation method and in the Corporate Level Strategy strategy by choosing a diversification method, the McDonalds company can ultimately increase revenue by maximizing the company's resources.